Modification of Cellulose Acetate Membrane in Textile Wastewater Treatment to Improve Antifouling Properties - Pramedikawati, Trias; Maryudi, Maryudi; Permadi, Adi; Mufrodi, Zahrul; Lestari, Riani Ayu (Universitas Tribhuwana Tunggadewi Malang, 2026)
The growth of the textile industry in Indonesia contributes positively to the economy, but simultaneously generates hazardous wastewater containing synthetic dyes and persistent organic compounds. The primary challenge in treating this effluent is fouling of cellulose acetate (CA) membranes, which reduces filtration efficiency and shortens operational lifespan due to pollutant accumulation. This study aims to evaluate various CA membrane modification strategies to enhance their physicochemical characteristics and antifouling properties. The discussion covers the integration of additives, including metal oxides (TiO?, ZnO), polymers (PEG, chitosan), and carbon-based materials (GO, CNT), which have been shown to form a stable hydration layer on the membrane surface. The review results indicate that these modifications significantly increase hydrophilicity, improve dye rejection up to 85 percent, and achieve a flux recovery ratio exceeding 90 percent. In conclusion, CA membrane modification via surface engineering is an effective solution for enhancing filtration performance and improving the sustainability of textile wastewater treatment.